EFFECTS OF FERTILIZATION ON POREWATER NUTRIENTS, GREENHOUSE-GAS EMISSIONS AND RICE PRODUCTIVITY IN A SUBTROPICAL PADDY FIELD. (26th February 2018) - WANG, WEIQI; SARDANS, JORDI; WANG, CHUN; TONG, CHUAN; JI, QINYANG; PEÑUELAS, JOSEP
SUMMARY: Suitable fertilization is crucial for the sustainability of rice production and for the potential mitigation of global warming. The effects of fertilization on porewater nutrients and greenhouse-gas fluxes in cropland, however, remain poorly known. We studied the effects of no fertilization (control), standard fertilization and double fertilization on the concentrations of porewater nutrients, greenhouse-gas fluxes and emissions, and rice yield in a subtropical paddy in southeastern China. Double fertilization increased dissolved NH4 + in porewater. Mean CO2 and CH4 emissions were 13.5% and 7.4%, and 20.4% and 39.5% higher for the standard and double fertilizations, respectively, than the control. N2 O depositions in soils were 61% and 101% higher for the standard and double fertilizations, respectively, than the control. The total global warming potentials (GWPs) for all emissions were 14.1% and 10.8% higher for the standard and double fertilizations, respectively than the control, with increasing contribution of CH4 with fertilization and a CO2 contribution > 85%. The total GWPs per unit yield were significantly higher for the standard and double fertilizations than the control by 7.3% and 10.9%, respectively. The two levels of fertilization did not significantly increase rice yield. Prior long-term fertilization in the paddy (about 20 years with annual doses of 95 kg N ha −1, 70 kg P2 O5 ha −1 and 70 kg K2 O ha −1 ) might have prevented these fertilizations from increasing the yield. However, fertilizations increased greenhouse-gas emissions. This situation is common in paddy fields in subtropical China, suggesting a saturation of soil nutrients and the necessity to review current fertilization management. These areas likely suffer from unnecessary nutrient leaching and excessive greenhouse-gas emissions. These results provide a scientific basis for continued research to identify an easy and optimal fertilization management solution.